2020
DOI: 10.3390/vaccines8020302
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Herpes Simplex Virus Infection and Vaccine Development

Abstract: Herpes simplex virus (HSV) infections are among the most common viral infections and usually last for a lifetime. The virus can potentially be controlled with vaccines since humans are the only known host. However, despite the development and trial of many vaccines, this has not yet been possible. This is normally attributed to the high latency potential of the virus. Numerous immune cells, particularly the natural killer cells and interferon gamma and pathways that are used by the body to fight HSV infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 158 publications
1
21
0
3
Order By: Relevance
“…Activation of the innate immune response relies upon the recognition of pathogen-associated molecular patterns (PAMPs) by specific pattern-recognition receptors (PRRs). Similar to findings in humans, Toll-like receptors (TLRs) and RIG-1-like receptors (RLRs) are the two main PRRs involved in the recognition of viral components [50]. There are several TLRs upregulated in response to viral infections (TLR4, TLR5, TLR15, TLR16) [51].…”
Section: Host Immune Responses To Ib and Nd 221 Host Immune Responmentioning
confidence: 74%
“…Activation of the innate immune response relies upon the recognition of pathogen-associated molecular patterns (PAMPs) by specific pattern-recognition receptors (PRRs). Similar to findings in humans, Toll-like receptors (TLRs) and RIG-1-like receptors (RLRs) are the two main PRRs involved in the recognition of viral components [50]. There are several TLRs upregulated in response to viral infections (TLR4, TLR5, TLR15, TLR16) [51].…”
Section: Host Immune Responses To Ib and Nd 221 Host Immune Responmentioning
confidence: 74%
“…Herpes simplex virus (HSV) is a common human pathogen, which initially infects orofacial mucosal surfaces and replicates in epithelial cells at these sites, causing clinically overt disease characterized by vesicular lesions ( 39 ). On one hand, HSV invasion is normally followed by activation of both the innate and adaptive immune systems ( 40 ). On the other hand, HSV develops different mechanisms, including inhibition of autophagy and apoptosis to avoid the immune system and maintain itself in latency ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, HSV invasion is normally followed by activation of both the innate and adaptive immune systems ( 40 ). On the other hand, HSV develops different mechanisms, including inhibition of autophagy and apoptosis to avoid the immune system and maintain itself in latency ( 40 ). This research revealed that Herpes simplex infection signaling pathway is also important in the regulation of E. tarda infection, and the constructed lncRNA–miRNA–mRNA networks shed new light on understanding the interplay of E. tarda infection and the intestinal mucosal immune responses of P. olivaceus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the first type of contribution, Anthony Ike and coworkers [ 11 ] describe the interplay between innate and adaptive immune responses activated during HSV infections to control virus replication and the different immune evasion strategies developed by the virus to avoid clearance and favor the establishment of latent infection. The Authors also provide an interesting overview of the main prophylactic and therapeutic vaccination strategies that have been developed to date against HSV infections (mainly against HSV-2), including live-attenuated, replication-defective, subunit and DNA vaccines and their stage of development.…”
mentioning
confidence: 99%